HUBUNGAN KINERJA GURU DENGAN MINAT BELAJAR PADA MATA PELAJARAN TDO SISWA KELAS X SMK NEGERI 1 TOMPASOBARU: HUBUNGAN KINERJA GURU DENGAN MINAT BELAJAR PADA MATA PELAJARAN TDO SISWA KELAS X SMK NEGERI 1 TOMPASOBARU - Kliuvert Simbala; Yohanis Rampo; Jemmy Kewas (GEARBOX: Jurnal Pendidikan Teknik Mesin, 2022)
As an important part of the world of education, the teacher's situation is seen as an important factor in achieving learning goals at school. This assumption depends on the understanding that the teacher is the person who manages the students in the learning system in the classroom, so the implication is that the educator is the individual who best understands and knows the condition and quality of his students, as one of the important things in the implementation of learning. The research method used is a quantitative research method, the method of collecting data is using a questionnaire or questionnaire. The data analysis techniques used in this study are regression analysis and hypothesis testing. Based on the results of the research on the relationship between teacher performance and interest in learning, the correlation value or relationship (R) is 0.530. This value is interpreted that the relationship between the two variables is a fairly strong category, from the table above the coefficient of determination (R Square) is 0.281 which implies that the relationship between teacher performance with interest in learning bound by 28.1% while for the rest 71.9% related to other variables not examined by researchers. Keywords: teacher performance relationship with learning interest